Development of cognitive processing speed through musical tools: A documentary review - Alonso Jartín, Ruth; Posse Robles, Damián Saúl (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The aim of this research is to assess, through documentary review, one of the fundamental aspects for learning and for the development of musical skills, such as processing speed (SP). In addition, cognitive stimulation (SC) and attention are addressed, as elements of the human being, which have significant learning. On the other hand, and for the achievement of musical content, a list of procedures for teaching sequencing and a mode of innovative tools, Music Mind Games, a musical language teaching system, inspired by the Suzuki methodology, is established.